PERUBAHAN SIFAT FISIKO –KIMIA DAGING LUMAT CUCUT DAN PARI AKBAT PENGARUH PENGKOMPOSISIAN DAN PENYIMPANAN DINGIN - Santoso, Joko; Nur Yasin, Ade Wiguna; Santoso, Santoso (Fakultas Perikanan dan Kelautan Universitas Riau, 2007)
This experiment was carried out to study the effects of leaching, composting andchill storage of shark and stingray mince on the correlation to physico-chemistryproperties changes.Three times leaching of mince fish could reduce the ureacontents of shark and stingray were 88% and 100%, respectively; with the saltsoluble protein contents were 13.52% and 13.24%, respectively. Mince fishcompositioning of shark and stingray in proportion 25%:75% gave the highestvalue of gel strength (209.29 g.cm). During chill storage of mince fish,deterioration process still occurred that indicated by increasing value of acidityand contents of base volatile compounds i.e. total volatile base nitrogen (TVBN);and tri-methyl amine (TMA); and also decreasing content of salt soluble proteinand gel forming ability.